ENGLISH LANGUAGE NEEDS ANALYSIS OF HOSPITALITY STUDENTS OF A VOCATIONAL HIGH SCHOOL: A CASE STUDY - Ariel Nuresa Budhitama, - (2021)
Hospitality is a field where communication skill is one of the most crucial aspects to be mastered since interactions with other people occur on a daily basis for anyone who works in that area. As the hospitality field deals with not only local tourists, but also foreign tourists, English has become a highly demanded language since English is a global language. However, English that is needed in the hospitality field is not as simple as English for general communication. Some attributes are specifically needed in English for the hospitality field. Therefore, as the students should be taught English is needed in the hospitality field, English for Specific Purposes will be an appropriate English to be taught to hospitality students because as has been defined by many ESP scholars, it is designed to fulfill the needs of the students. The current study seeks to find out English needs using target-situation analysis, and present-situation analysis, a framework proposed by Hutchinson & Waters (1987), for the students in the hospitality field. The study employed a case study method. The data were collected from the thirty-four 12th grade hospitality students by distributing the questionnaire, and from a teacher and hoteliers by conducting an interview. The result of the study revealed that all basic language skills, including vocabulary knowledge and grammar, have their extent in how they are needed by hospitality students. Listening and speaking are the most needed skills as they are involved in many tasks in the hospitality field. Reading and writing is the least needed skill as there are not many tasks that involve these skills. Vocabulary and grammar are needed as a foundation for other skills. The study also found that some skills need to be improved. Students need to improve their language skills, particularly speaking and listening skills, not only to be able to face some difficult tasks in the hospitality field but also to get a job in the hospitality field. students will find some difficult tasks in the hospitality field that require their language skills to be on a higher level. This study hopefully can become a reference for teachers in designing an English course for hospitality students.